2003
DOI: 10.1016/s0002-9440(10)63635-8
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Is Involved in the Degradation of Different Aquaporin-2 Mutants Causing Nephrogenic Diabetes Insipidus

Abstract: Mutations in the water channel aquaporin-2 (AQP2) can cause congenital nephrogenic diabetes insipidus. To reveal the possible involvement of the protein quality control system in processing AQP2 mutants, we created an in vitro system of clone 9 hepatocytes stably expressing endoplasmic reticulum-retained T126M AQP2 and misrouted E258K AQP2 as well as wild-type AQP2 and studied their biosynthesis, degradation, and intracellular distribution. Mutant and wild-type AQP2 were synthesized as 29-kd nonglycosylated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 48 publications
(65 reference statements)
5
33
0
Order By: Relevance
“…Consequently, mechanisms underlying subsequent degradation of the wild-type-mutant complexes of AQP2 and AE1 differ somewhat. Degradation of the dominant NDI-causing mutant E258K of AQP2 in clone 9 hepatocytes occurs rapidly in a proteasome-and lysosome-dependent manner (Hirano et al, 2003), whereas in cells transfected with the R664X mutant of AE1, the protein is principally degraded by the proteasomal pathway, as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Consequently, mechanisms underlying subsequent degradation of the wild-type-mutant complexes of AQP2 and AE1 differ somewhat. Degradation of the dominant NDI-causing mutant E258K of AQP2 in clone 9 hepatocytes occurs rapidly in a proteasome-and lysosome-dependent manner (Hirano et al, 2003), whereas in cells transfected with the R664X mutant of AE1, the protein is principally degraded by the proteasomal pathway, as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Mutant AQP2 molecules in dominant NDI can associate with wild-type AQP2, forming heterotetramers (Kamsteeg et al, 1999;Marr et al, 2002;Kamsteeg et al, 2003). This interaction causes retention in the Golgi complex and/or lysosomes (Mulders et al, 1998;Tamarappoo et al, 1999;Marr et al, 2002;Hirano et al, 2003) or mis-targeting of wild-type protein to the basolateral membrane (Kamsteeg et al, 2003;Asai et al, 2003), whereas AQP2 mutants in recessive NDI cannot associate with wild-type protein (Kamsteeg et al, 1999) and are retained in the ER (Deen et al, 1995;Mulders et al, 1997). Kamsteeg et al therefore suggested that AQP2 assembly into tetramers occurs after exit from the ER (Kamsteeg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of these mutations might involve Ser256, the residue that is phosphorylated by PKA prior to enhanced accumulation of AQP2 into the apical membrane. Whereas loss of Ser256 itself results in constitutive vesicularization of AQP2 and does not result in intracellular accumulation (van Balkom et al, 2002), loss of specific residues in close proximity to Ser256, including Glu258Lys does (Hirano et al, 2003). This suggests that there might be differential regulation of the phosphorylation at Ser256, such that two different functions of the protein can be alteredmembrane accumulation subsequent to PKA activity or intracellular trafficking -depending on which interaction is disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrate that the ubiquitin-proteasome degradation system affects the activity of some membrane transporters (11)(12)(13)(14)(15)(16). The system is responsible for the disposal of many of the short-lived proteins in eukaryotic cells (17)(18)(19).…”
mentioning
confidence: 99%